EMG Analysis During Static Balance in Chronic Ankle Instability, Coper and Controls - Han, Seunguk; Oh, Minsub; Lee, Hyunwook; Hopkins, J. Ty (International Journal of Sports Medicine, 2023)
Patients with chronic ankle instability (CAI) consistently display postural control alterations, which may result from sensorimotor dysfunction. This study aimed to compare muscle activity in the lower extremity and postural control among individuals with CAI, copers and uninjured controls during a static balance test. A total of 57 physically active participants were categorized into three groups (CAI, copers and controls) and performed a single-leg balance test with two visual conditions: eyes open and eyes closed. Muscle activity in six lower extremity muscles and center of pressure (CoP) variables were recorded and analyzed. Patients with CAI exhibited greater muscle activity in the medial gastrocnemius and gluteus maximus compared to controls or copers, regardless of the visual condition. Copers displayed increased gluteus medius activity compared to controls. Additionally, all groups demonstrated increased muscle activity and CoP variables when visual feedback was disrupted. These findings suggest that patients with CAI may have less effective recruitment of motor units during static balance. On the other hand, greater muscle activity in the gluteus medius in copers may represent a coping mechanism to avoid further ankle injuries. Further research on muscle activity during dynamic postural control is warranted to explore sensorimotor alterations in patients with CAI.
Keywords: chronic ankle instability; electromyograph; coper; postural control